The study of corrosion rate for carbon steel pipe in alkaline concrete solution - Mohd Faiz Muaz, Ahmad Zamri (2008)
Although preservative treatments prolong the life of carbon steel pipeline, they can also accelerate the corrosion of fasteners. This is an issue that needs to be studied because corrosion of building materials and fasteners can negatively affect system performance. In this study, the test methods examine the corrosion of metals in contact with aqueous are summarized and reviewed so that a comparison of their effectiveness can be made. Comparable results are obtained using the same method of study that is following the standard of ASTM Standard G31, “Standard Practice for Laboratory Immersion Corrosion Testing of Metals” principally to steel-water systems ( SOLTEQ, Corrosion study kits. Model BP 01), the apparatus is also suitable as a test bench for other chemical systems. Based on the results from the experiment it is stated that NaOH solution recorded the highest weight reduction that is 0.005 mg/cm 2 .day at pH 8 with the concentration of 0.000375 mole/L. In the temperature test at the same concentration and pH, corrosion rate of weight loss are very high that is 0.007 mg/cm 2 .day. The highest corrosion rate from overall experiment is when the dissolved oxygen concentration is 4.93 mg/L in the temperature range from 55 O C. When concentration of solution is decrease the weight reduction is increased The alkaline pH value is proportional to the value of concentration. At low pH the dissolved oxygen is reduced at the metal surface. Increasing the temperature will increase the ionic mobility and thus will increase the rate of oxygen diffusion to the metal surface and more oxygen is available to for cathodic reduction process. Plus increase viscosity and conductivity. When the DO is reduced oxygen reduction and hydrogen evolution become the prevalent to cathodic reaction and the corrosion is further accelerated.